A thermally conductive composite hydrogel containing a liquid metal network and a preparation method thereof
Through the composite of liquid metal network and hydrogel, the problems of low thermal conductivity and insufficient flexibility of existing thermal conductivity materials are solved, and the thermal composite hydrogel with high thermal conductivity and flexibility is achieved, suitable for smart skin and flexible heat dissipation bodies and other fields.
Patent Information
- Application Number
- CN202110978797.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-08-25
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2041-08-25
AI Technical Summary
The existing thermal conductivity of thermal polymer composites is relatively low and lacks flexibility, making it difficult to meet the application needs of smart skin and flexible heat dissipation bodies.
The composite of liquid metal network and hydrogel is adopted to form a liquid metal network through template freezing, and polymer hydrogel is cast at low temperature to form a thermally conductive composite hydrogel wrapped in liquid metal, ensuring that the thermally conductive network can flow at room temperature and Stay continuous.
It achieves high thermal conductivity and good flexibility, can quickly transfer and absorb heat, reduce interface thermal resistance, improve heat transfer efficiency, and is suitable for surface bonding of complex parts.
Smart Images

Figure CN115716923B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thermal conductive materials, and in particular relates to a thermal conductive composite hydrogel containing a liquid metal network and a preparation method thereof. Background Art
[0002] With the continuous enhancement and improvement of the functions and integration of 5G communications, electronic chips, artificial intelligence, etc., the heat generation power and heat density of device equipment are also getting higher and higher. Effective cooling of devices is crucial to ensure their safe and efficient operation and extend their service life. [1-3] Surveys show that more than 50% of electronic equipment failures are caused by overheating [4] . The service life of electronic devices is exponentially related to their operating temperature. When the operating temperature increases by 10-15°C, the service life of electronic equipment can be reduced by 2 times; a 1°C reduction in the operating temperature of the component will result in a 4% reduction in its failure rate. Therefore, thermal management is the main focus of today's electronic equipment. Traditional thermal conductive materials include metals, inorganic ceramics, graphite and other materials. However, metals have poor chemical corrosion resistance, ceramic materials have high processing costs and poor impact resistance, and materials such as graphite have poor mechanical properties, which can no longer meet the current development requirements of industry and science and technology. Polymer composites filled with high thermal conductivity fillers have become the development direction of the field of thermal conductive materials in recent years because of their advantages of low density, excellent mechanical properties, good processing performance and high thermal conductivity. They have broad application prospects in the fields of energy, communications, electronics and other fields. [5-7] .
[0003] However, the matrix of existing thermal conductive polymer composite materials is mostly highly elastic materials such as epoxy resin and silicone rubber, which lacks flexibility, limiting their application in the fields of smart skin, flexible heat sinks, etc.
[0004] Hydrogel is a soft polymer material with a large amount of water as the dispersion medium. It has broad application prospects in the field of wearable electronics. [8] After being filled with high thermal conductivity fillers, it can also be used in the field of thermal conductivity. The key to improving the thermal conductivity of polymer materials lies in whether the fillers form a large number of continuous pathways inside the matrix and whether they can exist stably. [9] However, the commonly used high thermal conductivity networks are mostly solid, which is not compatible with the mechanical properties of hydrogels. Liquid metal is a type of metal that is liquid at room temperature. It has both the high thermal conductivity of metal and the fluidity of liquid.
[10] The thermally conductive composite hydrogel formed by constructing a high thermal conductivity network with liquid metal and casting hydrogel has high thermal conductivity, good flexibility and excellent mechanical properties.
[0005] In addition, the high specific heat capacity of the hydrogel combined with the high thermal conductivity of the liquid metal network allows heat to not only be quickly transferred in the liquid metal network, but also be absorbed by the hydrogel and then gradually released, avoiding damage to the device due to excessive local temperature. This is of great significance for expanding the performance and application of thermally conductive composite materials.
[0006] References
[0007] [1]Theis TN, Wong H P. The End of Moore's Law: A New Beginning for Information Technology[J]. Computing in Science&Engineering, 2017, 19(2): 41-50.
[0008] [2] Schelling PK, Shi L, Goodson K E.Managing heat for electronics.Mater.Today 2005, 8, 30-35.
[0009] [3]Pu S, Fu J, Liao Y, Ge L, Zhou Y, Zhang S, Zhao S, Liu X, Hu X, Liu K, ChenJ. Promoting energy efficiency via a selfadaptive evaporative coolinghydrogel. Adv.Mater.2020, 32, 1907307.
[0010] [4] Chu Jiurong, Zhang Xiaohui, Xu Chuanxiang. Research and application of thermal conductive polymer materials [J]. Polymer Materials Science and Engineering, 2000, 16(4): 17-21.
[0011] [5] Mamunya YP, Davydenko VV, Pissis P, Lebedev EV. Electrical and thermalconductivity of polymers filled with metal powders. Eur Polym J 2002; 38: 1887-1897.
[0012] [6] Wu Y, Yu Z. Thermal conductivity of in situ epoxy composites filled with Zrb2 particles. Compos Sci Technol 2015;107:61-66.
[0013] [7] Hu J, Huang Y, Yao Y, Pan G. Polymer composite with improved thermalconductivity by constructing a hierarchically ordered three-dimensional interconnected network of BN. ACS Appl Mater Interfaces 2017;9(15):13544-13553.
[0014] [8] Z. Chen, D. Zhao, B. Liu, G. Nian, X. Li, J. Yin, S. Qu, W. Yang, Adv. Funct. Mater. 2019, 29, 1900971.
[0015] [9] Liu Shaogang, Wang Libo, Wang Xiaolong, et al. Research progress of high thermal conductivity network polymer matrix composites[J]. China Plastics, 2019, 33(8): 127-135.
[0016]
[10] Yuji Gao, Hiroki Ota, Ethan W. Schaler, Kevin Chen, Allan Zhao, Wei Gao, Hossain M. Fahad, Yonggang Leng, Anzong Zheng, Furui Xiong, Chuchu Zhang, Li-Chia Tai, Peida Zhao, Ronald S. Fearing, Ali Javey. Advanced Materials. 2017, 1701985. Summary of the invention
[0017] In view of the problems of low thermal conductivity and lack of flexibility of existing polymer composite materials, the purpose of the present invention is to provide a thermally conductive composite hydrogel containing a liquid metal network and a preparation method thereof.
[0018] The purpose of the present invention is achieved through the following technical solutions.
[0019] The thermally conductive composite hydrogel containing a liquid metal network is characterized in that: liquid metal is filled in the flow channel of a template and is frozen at low temperature to form a solid phase liquid metal network; a polymer solution before gelation is cast into the liquid metal network at low temperature, and after gelation, a thermally conductive composite hydrogel wrapping the liquid metal network is formed; at room temperature, the liquid metal forms a flowable thermally conductive network, and the thermally conductive composite hydrogel remains in a continuous state after being deformed by an external force.
[0020] A method for preparing a thermally conductive composite hydrogel containing a liquid metal network comprises the following steps:
[0021] 1) coating liquid metal on a template with a flow channel on its surface, placing the template coated with liquid metal in a negative pressure environment with an absolute pressure of 0.1 to 10 KPa for 5 to 60 minutes, so that the liquid metal enters the flow channel; the liquid metal is a metal / alloy that is liquid at room temperature, and may be gallium, gallium-indium alloy, or gallium-indium-tin alloy; the template is a template with high wettability of liquid metal, and its material may be inorganic silicon, stainless steel, organic silicon, polytetrafluoroethylene, polyvinylidene fluoride, or polyethylene terephthalate; the flow channel is a groove with different patterns having a groove width and a groove depth of 100 to 1000 microns, and the pattern may be a straight line, a parallel double straight line, a parallel triple straight line, a cross, a well, or a spiral (see attached Figure 2-7 );
[0022] 2) scraping off the excess liquid metal on the surface of the template, placing the template at -10 to -50°C for 1 to 24 hours to solidify the liquid metal to obtain a solid phase liquid metal; separating the liquid metal from the template to obtain a liquid metal solid phase network;
[0023] 3) Dissolving the polymer hydrogel precursor in water to prepare an aqueous solution of the polymer hydrogel precursor with a mass fraction of 1 to 50%, which is referred to as solution A; treating the above solution A at an absolute pressure of less than 0.1 MPa for 10 to 60 minutes to remove bubbles. The mass fraction of water in the polymer hydrogel is not less than 50%, and the polymer hydrogel can be polyvinyl alcohol, polyethylene glycol or cellulose hydrogel;
[0024] 4) placing the liquid metal solid phase network in a mold under a temperature of -10 to -50°C, casting solution A, and cooling the solution A at this temperature for 1 to 24 hours to gelate the solution A to form a hydrogel, wherein the formed hydrogel and the liquid metal solid phase network obtained in 2) together form a thermally conductive composite hydrogel containing a liquid metal network; wherein the mold is a splint containing a sealing ring (see attached Figure 8 ).
[0025] 5) slightly heating the thermally conductive composite hydrogel obtained in 4) at 25 to 35° C. to restore the liquid metal to a liquid phase, and soaking the thermally conductive composite hydrogel in deionized water at room temperature for 1 to 48 hours to remove impurities in the hydrogel network;
[0026] 6) Test the thermal conductivity of the thermally conductive composite hydrogel.
[0027] The specific instructions are as follows:
[0028] The main matrix in the heat-conductive composite hydrogel containing a liquid metal network of the present invention is a hydrogel. Different from the traditional matrix epoxy resin, the hydrogel contains a large amount of water, which enables it to quickly exchange heat through local convection. In addition, the high specific heat capacity of water itself enables the hydrogel to first absorb a large amount of heat transferred by the liquid metal network and then gradually release it. In addition, hydrogen bonds are formed between the hydrogel matrix molecules in the composite hydrogel of the present invention, which is conducive to quickly transferring the heat in the hydrogel to the liquid metal network, and then the heat is quickly propagated along the liquid metal network, so that the composite hydrogel exhibits excellent thermal conductivity. Moreover, the composite hydrogel of the present invention has better flexibility than traditional epoxy resin and other materials, and can better fit with the surface of complex parts, which is conducive to reducing interfacial thermal resistance and improving heat transfer efficiency.
[0029] Beneficial effects of the present invention:
[0030] The raw materials of the invention are simple and easy to obtain. Through simple template freezing, a liquid metal network can be formed. The liquid metal heat-conducting network can flow at room temperature and has good thermal conductivity. After being deformed by external force, the heat-conducting network is still continuous and effective. The high specific heat capacity of the hydrogel is conducive to the material absorbing the heat transferred by the liquid metal network first and then gradually releasing it. The obtained polymer composite material has excellent flexibility and thermal conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Schematic diagram of the structure of the thermally conductive composite hydrogel containing a liquid metal network
[0032] Figure 2 Schematic diagram of the straight runner template
[0033] Figure 3 Schematic diagram of the parallel double straight runner template
[0034] Figure 4 Schematic diagram of parallel three-line flow channel template
[0035] Figure 5 Schematic diagram of the cross flow channel template
[0036] Figure 6 Schematic diagram of the tic-tac-toe flow channel template
[0037] Figure 7 Schematic diagram of the spiral flow channel template
[0038] Figure 8 Schematic diagram of the hydrogel molding mold DETAILED DESCRIPTION
[0039] Sources of purchase of medicines and materials:
[0040] Gallium, gallium-indium alloy, and gallium-indium-tin alloy, with a purity of 99.99%, were purchased from Tianjin Hongfeng Weili Technology Development Co., Ltd.;
[0041] Polyvinyl alcohol, polyethylene glycol, cellulose and other hydrogel precursors were purchased from Tianjin Shengshiwoda Technology Co., Ltd.;
[0042] Templates such as inorganic silicon, stainless steel, organic silicon, polytetrafluoroethylene, polyvinylidene fluoride, and polyethylene terephthalate were purchased from the Weiwang microfluidic experimental platform;
[0043] The splint with sealing ring was purchased from Xi'an Weiketu Rui Biotechnology Co., Ltd.;
[0044] The silicone gasket was purchased from Tianjin Yanhui Technology Co., Ltd.
[0045] Thermal conductivity test: The material was processed into samples with a side length of 30 mm and a thickness of 2 mm, and the thermal conductivity of the composite material was tested using a hot-disk thermal constant analyzer.
[0046] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0047] Example 1
[0048] 1) Liquid metal gallium is coated on an inorganic silicon template with a groove width of 100 microns and a straight-line pattern on the surface, and the inorganic silicon template coated with liquid metal is treated in a negative pressure environment with an absolute pressure of 0.1 KPa for 5 minutes to allow the liquid metal to enter the flow channel;
[0049] 2) scraping off the excess gallium on the surface of the template, placing the template at -10°C for 1 hour to solidify the gallium to obtain solid-phase gallium; separating the gallium from the organosilicon template to obtain a gallium solid-phase network;
[0050] 3) dissolving polyvinyl alcohol in water to prepare a 1% aqueous solution, which is referred to as solution A; treating the solution A at an absolute pressure of 0.01 MPa for 10 min to remove bubbles;
[0051] 4) placing the gallium solid phase network in a clamping plate mold containing a sealing ring at -10°C, casting solution A, and cooling the solution A at this temperature for 1 hour to gelate solution A to form a polyvinyl alcohol hydrogel. The formed hydrogel and the gallium solid phase network obtained in 2) together form a thermally conductive composite hydrogel containing a liquid metal network;
[0052] 5) slightly heating the thermally conductive composite hydrogel obtained in 4) at 35° C. to restore gallium to a liquid phase, and immersing the thermally conductive composite hydrogel in deionized water at room temperature for 1 hour to remove impurities in the hydrogel network;
[0053] 6) The thermal conductivity of the thermally conductive composite hydrogel was measured to be 1.2 W / mK.
[0054] Example 2
[0055] 1) Liquid metal gallium is coated on a stainless steel template with a parallel double-line pattern and a groove width of 1000 microns on the surface, and the stainless steel template coated with liquid metal is placed in a negative pressure environment with an absolute pressure of 0.9 KPa for 10 minutes to allow the liquid metal to enter the flow channel;
[0056] 2) scraping off the excess gallium on the surface of the template, placing the template at -10°C for 2 hours to solidify the gallium to obtain solid-phase gallium; separating the gallium from the stainless steel template to obtain a gallium solid-phase network;
[0057] 3) dissolving polyethylene glycol in water to prepare a 50% aqueous solution, referred to as solution A; treating the solution A at an absolute pressure of 0.02 MPa for 10 min to remove bubbles;
[0058] 4) placing the gallium solid phase network in a clamping mold containing a sealing ring at -10°C, casting solution A, and cooling the solution A at this temperature for 4 hours to gelate solution A to form a polyethylene glycol hydrogel. The formed hydrogel and the gallium solid phase network obtained in 2) together form a thermally conductive composite hydrogel containing a liquid metal network;
[0059] 5) slightly heating the thermally conductive composite hydrogel obtained in 4) at 35° C. to restore gallium to a liquid phase, and immersing the thermally conductive composite hydrogel in deionized water at room temperature for 10 hours to remove impurities in the hydrogel network;
[0060] 6) The thermal conductivity of the thermally conductive composite hydrogel was measured to be 1.4 W / mK.
[0061] Example 3
[0062] 1) coating liquid metal gallium-indium alloy on a silicone template with a cross pattern and a groove width of 100 microns, placing the silicone template coated with liquid metal in a negative pressure environment with an absolute pressure of 10 KPa for 20 minutes to allow the liquid metal to enter the flow channel;
[0063] 2) scraping off the excess gallium-indium alloy on the surface of the template, placing the template at -30°C for 8 hours to solidify the gallium-indium alloy to obtain a solid-phase gallium-indium alloy; separating the gallium-indium alloy from the organic silicon template to obtain a gallium-indium alloy solid-phase network;
[0064] 3) dissolving cellulose in water to prepare a 15% aqueous solution, referred to as solution A; treating the solution A at an absolute pressure of 0.02 MPa for 30 min to remove bubbles;
[0065] 4) placing the gallium-indium alloy solid phase network in a clamping mold containing a sealing ring at -30°C, casting solution A, and cooling at this temperature for 8 hours to gel solution A to form a cellulose hydrogel. The formed hydrogel and the gallium-indium alloy solid phase network obtained in 2) together form a thermally conductive composite hydrogel containing a liquid metal network;
[0066] 5) slightly heating the thermally conductive composite hydrogel obtained in 4) at 30° C. to restore the gallium-indium alloy to a liquid phase, and immersing the thermally conductive composite hydrogel in deionized water at room temperature for 20 hours to remove impurities in the hydrogel network;
[0067] 6) The thermal conductivity of the thermally conductive composite hydrogel was measured to be 1.5 W / mK.
[0068] Example 4
[0069] 1) coating liquid metal gallium-indium alloy on a polytetrafluoroethylene template with a groove width of 1000 microns and a tic-tac-toe pattern on the surface, placing the polytetrafluoroethylene template coated with liquid metal in a negative pressure environment with an absolute pressure of 5 KPa for 30 minutes to allow the liquid metal to enter the flow channel;
[0070] 2) scraping off the excess gallium-indium alloy on the surface of the template, placing the template at -30°C for 12 hours to solidify the gallium-indium alloy to obtain a solid-phase gallium-indium alloy; separating the gallium-indium alloy from the polytetrafluoroethylene template to obtain a gallium-indium alloy solid-phase network;
[0071] 3) dissolving polyvinyl alcohol in water to prepare a 10% aqueous solution, which is referred to as solution A; treating the solution A at an absolute pressure of 0.02 MPa for 30 minutes to remove bubbles;
[0072] 4) placing the gallium-indium alloy solid phase network in a clamping mold containing a sealing ring at -30°C, casting solution A, and cooling the solution A at this temperature for 12 hours to gelate solution A to form a polyvinyl alcohol hydrogel. The formed hydrogel and the gallium-indium alloy solid phase network obtained in 2) together form a thermally conductive composite hydrogel containing a liquid metal network;
[0073] 5) slightly heating the thermally conductive composite hydrogel obtained in 4) at 30° C. to restore the gallium-indium alloy to a liquid phase, and immersing the thermally conductive composite hydrogel in deionized water at room temperature for 30 hours to remove impurities in the hydrogel network;
[0074] 6) The thermal conductivity of the thermally conductive composite hydrogel was measured to be 1.8 W / mK.
[0075] Example 5
[0076] 1) coating liquid metal gallium indium tin alloy on a polyvinylidene chloride template with a parallel three-line pattern and a groove width of 100 microns, placing the polyvinylidene chloride template coated with liquid metal in a negative pressure environment with an absolute pressure of 2KPa for 45 minutes to allow the liquid metal to enter the flow channel;
[0077] 2) scraping off the excess gallium indium tin alloy on the surface of the template, placing the template at -50°C for 20 hours to solidify the gallium indium tin alloy to obtain a solid-phase gallium indium tin alloy; separating the gallium indium tin alloy and the polyvinylidene chloride template to obtain a gallium indium tin alloy solid-phase network;
[0078] 3) dissolving polyethylene glycol in water to prepare a 20% aqueous solution, referred to as solution A; treating the solution A at an absolute pressure of 0.02 MPa for 60 min to remove bubbles;
[0079] 4) placing the gallium indium tin alloy solid phase network in a clamping plate mold containing a sealing ring under a -50°C environment, casting solution A, and cooling the solution A at this temperature for 18 hours to gelate solution A to form a polyethylene glycol hydrogel. The formed hydrogel and the gallium indium tin alloy solid phase network obtained in 2) together form a thermally conductive composite hydrogel containing a liquid metal network;
[0080] 5) slightly heating the thermally conductive composite hydrogel obtained in 4) at 25° C. to restore the gallium-indium-tin alloy to a liquid phase, and soaking the thermally conductive composite hydrogel in deionized water at room temperature for 40 hours to remove impurities in the hydrogel network;
[0081] 6) The thermal conductivity of the thermally conductive composite hydrogel was measured to be 1.7 W / mK.
[0082] Example 6
[0083] 1) coating liquid metal gallium indium tin alloy on a polyethylene terephthalate template with a spiral pattern and a groove width of 1000 microns, placing the polyethylene terephthalate template coated with liquid metal in a negative pressure environment with an absolute pressure of 0.1 KPa for 60 minutes to allow the liquid metal to enter the flow channel;
[0084] 2) scraping off the excess gallium indium tin alloy on the surface of the template, placing the template at -50°C for 24 hours to solidify the gallium indium tin alloy to obtain a solid-phase gallium indium tin alloy; separating the gallium indium tin alloy from the polyethylene terephthalate template to obtain a gallium indium tin alloy solid-phase network;
[0085] 3) dissolving cellulose in water to prepare a 20% aqueous solution, referred to as solution A; treating the solution A at an absolute pressure of 0.02 MPa for 30 minutes to remove bubbles;
[0086] 4) placing the gallium indium tin alloy solid phase network in a clamping plate mold containing a sealing ring at -50°C, casting solution A, and cooling at this temperature for 24 hours to gel solution A to form a cellulose hydrogel. The formed hydrogel and the gallium indium tin alloy solid phase network obtained in 2) together form a thermally conductive composite hydrogel containing a liquid metal network;
[0087] 5) slightly heating the thermally conductive composite hydrogel obtained in 4) at 25° C. to restore the gallium-indium-tin alloy to a liquid phase, and immersing the thermally conductive composite hydrogel in deionized water at room temperature for 48 hours to remove impurities in the hydrogel network;
[0088] 6) The thermal conductivity of the thermally conductive composite hydrogel was measured to be 1.9 W / mK.
[0089] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A thermally conductive composite hydrogel containing a liquid metal network, characterized in that: The method comprises the following preparation steps: 1) coating liquid metal on a template with a flow channel on the surface, placing the template coated with liquid metal in a negative pressure environment with an absolute pressure of 0.1 to 10 KPa for 5 to 60 minutes, so that the liquid metal enters the flow channel; the template flow channel is a groove with a groove width and a groove depth of 100 to 1000 microns and different patterns, and the pattern is a straight line, a parallel double straight line, a parallel triple straight line, a cross, a well or a spiral; 2) scraping off the excess liquid metal on the surface of the template, placing the template at -10 to -50°C for 1 to 24 hours to solidify the liquid metal to obtain a solid phase liquid metal; separating the liquid metal from the template to obtain a liquid metal solid phase network; 3) dissolving the polymer hydrogel precursor in water to prepare an aqueous solution of the polymer hydrogel precursor with a mass fraction of 1 to 50%, which is referred to as solution A; treating the solution A at an absolute pressure of less than 0.1 MPa for 10 to 60 minutes to remove bubbles; 4) placing the liquid metal solid phase network in a mold under a temperature of -10 to -50°C, casting solution A, and cooling the solution A at the temperature for 1 to 24 hours to gelate the solution A to form a hydrogel, wherein the formed hydrogel and the liquid metal solid phase network obtained in 2) together form a thermally conductive composite hydrogel containing the liquid metal network; the mold is a splint containing a sealing ring; 5) Slightly heating the thermally conductive composite hydrogel obtained in 4) at 25-35° C. to restore the liquid metal to a liquid phase, and immersing the thermally conductive composite hydrogel in deionized water at room temperature for 1-48 hours to remove impurities in the hydrogel network.
2. The thermally conductive composite hydrogel containing a liquid metal network according to claim 1, characterized in that: The liquid metal is a metal / alloy that is liquid at room temperature, and is gallium, gallium-indium alloy, or gallium-indium-tin alloy.
3. The thermally conductive composite hydrogel containing a liquid metal network according to claim 1, characterized in that: The template is a template with high wettability of liquid metal, and its material is inorganic silicon, stainless steel, organic silicon, polytetrafluoroethylene, polyvinylidene chloride or polyethylene terephthalate.
4. The thermally conductive composite hydrogel containing a liquid metal network according to claim 1, characterized in that The hydrogel is polyvinyl alcohol, polyethylene glycol or cellulose.
5. The thermally conductive composite hydrogel containing a liquid metal network according to claim 1, characterized in that: At room temperature, the liquid metal thermal conductive network is flowable and has good thermal conductivity. After being deformed by external force, the thermal conductive network remains continuous and effective. The high specific heat capacity of the hydrogel is conducive to the material first absorbing the heat transferred by the liquid metal network and then gradually releasing it.
